Pemenuhan Hak Biologis Narapidana dalam Mempertahankan Perkawinan pada Lembaga Pemasyarakatan Kelas I Makassar: Analisis Maqashid al-Syariah - Yunus, Nur Arfianty; Akmal, Andi Muhammad; Qayum, Abdul Rahman; Shuhufi, Nadyatul Hikmah (Universitas Islam Negeri Alauddin Makassar, 2024)
This study aims to explore and analyze the fulfillment of the biological rights of prisoners who maintain marriage in Makassar Class I Penitentiary using the Maqashid al-Sharia approach. This research was conducted through field studies and primary and secondary data collection. The main focus is to identify and evaluate the implementation of the biological rights of prisoners in the context of maintaining marriage in a prison environment. In the context of Maqashid al-Sharia, the concept of biological rights of prisoners, considers the principles of justice and balance in Islam. This study provides a comprehensive picture of how prisons in Makassar Class I treat inmates who try to maintain their marriages. In addition, this study also explains the impact and relevance of the fulfillment of biological rights on the welfare of prisoners and marital stability. The concept of fulfilling the biological rights of prisoners in review from Maqashid al-Sharia is carried out according to their respective capabilities. Unlike the case if the husband or wife is a prisoner who must languish in bars, of course, the fulfillment of biological rights cannot be optimized. The results showed that the reality of fulfilling the biological rights of prisoners in Makassar class I correctional institutions was limited based on the policy that applies to prisoners who still have a legal marriage bond only limited to visiting and communicating by telephone in order to maintain household harmony. The fulfillment of prisoners' biological rights in maintaining marriage in Makassar Class I Penitentiary has its own challenges, such as limited facilities and internal regulations of the institution. Maqashid al-Sharia's analysis provides a critical view of the implementation of prisoners' biological rights, emphasizing the importance of justice and fair treatment in accordance with Islamic principles.